Geschlecht und Arbeitsmarkt: Gleichstellungspolitik in den USA und der Bundesrepublik - von Wahl, Angelika (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The article discusses different approaches of equal employment policy and investigates the implementation of such policies in the USA and in Germany. The conceptual differences of the applied policies point to dissimilar concepts of »equality« in Germany and in the USA.